Formação continuada em música: reconstruindo conhecimentos musicais e pedagógico-musicais com professoras unidocentes - Araújo, Gabriela da Ros de (2012)
This research is part of the line Education and Arts (LP4) Program Graduate Education / UFSM and integrates the research group FAPEM: training, action and research in music education (CNPq). The musical training of teachers in early childhood education has been the focus of research, due to the possibility that significant work to develop a professional music with children. Since the approval and enforcement of Law No. 11.769/08, there was an increase in supply and demand for continuing education courses in music, in order to expand and qualify the practice in the school and to enforce that law. Whereas continuing education can be a special area of research on the learning of teaching, this study aimed to investigate how to represent and reconstruct the knowledge of music and educational music-teacher teachers in early childhood education from an area of continuing education organized in school. The weekly educational meetings were used for the development of continuing education activities that sought to know which knowledge of music and music-teaching can be mobilized in a formative space like this, and understand the group's role in each teacher's professional development. Eight meetings were held with the group of teachers EMEI Borges, which addressed specific issues of teaching music in kindergarten. Qualitative, this research used as methodological resources focus group discussions, story-interview and impressions of the researcher on the development of continuing education and teachers. Based on studies of Ferry (2004), Josso (2010), Mizukami (2008), Mizukami et al (2002), Pivetta and Isaia (2009) and Bolzan (2009), we felt an awareness of teachers about each function that develops in the learning process of teaching. From this moment, the group constitutes a space of exchange and shared learning. In addition, the teachers have advanced the understanding of music as a specific area of knowledge and began to develop more practical musical intentionality and safety with children.